2016
DOI: 10.1016/j.jos.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The future of medical reimbursement for orthopedic surgery in Japan from the viewpoint of the health economy

Abstract: If medical professionals such as orthopedic surgeons contribute to the economic value of orthopedic surgery, it is crucial to clearly establish interventions among the different performances of medical reimbursement to motivate the increased allocation of management resources. To further develop this concept, discussions between stakeholders should involve the value of medicine based on cost and benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our findings concur that some patients with spinal stenosis may face high treatment costs, require frequent medical visits, and need to seek financial supports. Although our results cannot be generalized to all patients with spinal stenosis, it underscores the importance of proper social welfare support, reasonable healthcare costs, effective diagnosis and treatments, as well as sharing decision making for patients with spinal stenosis [10,[60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 81%
“…Our findings concur that some patients with spinal stenosis may face high treatment costs, require frequent medical visits, and need to seek financial supports. Although our results cannot be generalized to all patients with spinal stenosis, it underscores the importance of proper social welfare support, reasonable healthcare costs, effective diagnosis and treatments, as well as sharing decision making for patients with spinal stenosis [10,[60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 81%
“…With the global economic recession, the burden of medical expenses has become a social problem. 17 Compared with other cuff repair patterns, the suture-bridge procedure has a greater surgical cost. 18 Terhune et al.…”
Section: Discussionmentioning
confidence: 99%
“…Such high costs laid heavy burdens on individuals and the society, which also demonstrated that the distribution of medical resources was not so fair. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%